Think before you look : avoiding the consequences of secret temptation - Henderson, Daniel (Chattanooga, Tenn. : Living Ink Books, a division of AMG Publishers, 2005)
40 powerful reasons to rise above temptation. The treacherous sea of pornography is drowning millions of young and middle-aged men. Research indicates that sixty percent of Christian men are addicted to pornography. Most are naive and unprepared as they journey into the attractive but deadly waters. The best approach to helping men with this struggle is to give them strong preventive tools. Think Before You Look: Avoiding the Consequences of Secret Temptation provides a useful and timeless approach to avoiding the temptations of pornography before it is too late. The book is unique because the title does not presume guilt. The content springs from the author's experiences working with thousands of men and counseling many about the painful issues revolving around the porn industry. Each brief chapter explains the practical rationale and biblical basis for steering clear of pornography's clutches. Each chapter is succinct, sometimes humorous; yet meaty enough to offer sold biblical equipping for the battle. The approach avoids academic and clinical terminology. Instead, the writing is fast-paced, direct, and designed to lead to further personal or group Bible study. Think Before You Look promises to help the drowning and warn those considering the shadowy water.
nbl-09 rel
Keywords: Pornography -- Religious aspects -- Christianity; Temptation